IDENTIFIKASI MANFAAT HUTAN OLEH MASYARAKAT DESA KARUNIA KECAMATAAN PALOLO KABUPATEN SIGI - Sulham, Sulham; Umar, Syukur; Maiwa, Arman; Anwar, Anwar; Rahman, Abdul (Universitas Tadulako, 2021)
The pattern of utilization of forest products in rural areas has two social dimensions that influence the existence of forest areas. The First Dimension is that most rural people who consume forest products come from forest areas. The second social dimension is the existence of community dynamics, especially an increase in the population in an area and an increase in income and the quality of human resources that cause changes in the use of forest products. The purpose of this research is to find out how the Community in Utilizing Forest Products and Utilizing Forest Land in Karunia Village, Palolo District, Sigi Regency. The usefulness of this research is to provide information to the public about how the community in utilizing forest products and utilizing forest land in Karunia village, Palolo sub-district, Sigi district. This research was conducted in Karunia Village, Palolo District, Sigi Regency, Central Sulawesi Province. The time of this study is 2 (two) months, namely from October to December 2018. This study uses data collection (interview). To see the level of social capital using qualitative descriptive analysis. In this study there were 39 respondents in Karunia village. The results of this study show the overall activity of the Karunia Village community in protected forest areas in Karunia Village is to harvest timber as a material for making and repairing homes and firewood, harvesting rattan, bamboo, candlenut, honey bees and other forest products. Village Community Activities Karunia Making Use of Forest Land in Protected Forests is Gardening and Farming such as planting cocoa, Durian, Langsat, Banana, Rambutan and Coffee.Keywords: Benefits of Forest and Forest Land Products by Communities in Karun Village